2015
DOI: 10.1155/2015/486510
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Biochemical Evaluation of the Kidney following Chronic Consumption of Hibiscus sabdariffa

Abstract: Hibiscus sabdariffa L. has been used traditionally as herbal medicine and has been documented to have a broad range of therapeutic effects. The present study aimed to investigate the effects of chronic administration of aqueous extract of flowers of Hibiscus sabdariffa on the histology of the kidney and some biochemical indices of renal function in male Wistar rats. Twenty (20) Wistar rats were randomly divided into four (4) groups of five rats each. The extract was administered orally in doses 200, 500, and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
2
1
1
Order By: Relevance
“…In female volunteers, the number of BUN levels remained at the same levels either on day 30 or day 45. The increased levels of BUN in women was in line with those reported by Ukoha et al [35], indicating that the increased BUN is due to an integrity distortion of renal cytoarchitecture in the administration of rosella flower water extract for 21 days. It is because rosella has a diuretic effect, caused by quercetin and anthocyanin [36].…”
Section: The Effect Of Ethanolic Extract Of Rosella On Bunsupporting
confidence: 90%
“…In female volunteers, the number of BUN levels remained at the same levels either on day 30 or day 45. The increased levels of BUN in women was in line with those reported by Ukoha et al [35], indicating that the increased BUN is due to an integrity distortion of renal cytoarchitecture in the administration of rosella flower water extract for 21 days. It is because rosella has a diuretic effect, caused by quercetin and anthocyanin [36].…”
Section: The Effect Of Ethanolic Extract Of Rosella On Bunsupporting
confidence: 90%
“…5). A similar trend to this model of apoptosis was caused by the chronic consumption of Chili pepper [36]. Apoptosis is a mode of cell death characterized by specific morphological and biochemical features [34].…”
Section: Discussionsupporting
confidence: 61%
“…High protein intake could cause an increased level of ureum and creatinine. Although, this result showed no significant difference on histological of the kidney, using of rosella for a long duration, need special attention as previous research reported the kidney damage on higher dose 25 . Treatment higher dose 200, 500, dan 800 mg/kg.bw of rosella extract for 21 days reported to cause the biochemical of renal shown by the increasing of ureum and creatinine and also the histopathological of the kidney.…”
Section: Fig 1: Histopathological Profile Of Rat Kidney Which Subchrcontrasting
confidence: 52%